Das políticas de formação às percepções do processo formativo e da prática alfabetizadora - Pinto, Érika Giuliana Rodrigues Pires (2020)
This research focuses on understanding the training process of literacy teachers based on the teacher training program National Pact for Literacy at the Right Age (Pacto Nacional pela Alfabetização na Idade Certa - PNAIC). This integrated program aims to teach literacy until the 3rd year of elementary school (8 years of age) to all children from Brazilian municipal and state, urban and rural, schools. The program integrates and structures the continuing education of leading literacy teachers. In this sense, the research seeks to answer what does the PNAIC training program contribute to literacy teacher regarding reading and writing practices, and to what extent can the actions performed by literacy teachers towards innovations in literacy and literacy practices be related to the pedagogical guidelines proposed by this program. Therefore, this study proposed to analyze what the literacy teachers find prominent regarding the PNAIC training program and verify what perceptions the teachers build regarding the training process and literacy practice. This study consists of field research with a qualitative approach using a data collection technique a questionnaire applied to 10 teachers from a public elementary school in a municipality in the countryside of Minas Gerais, Brazil. The proposal was to portray the PNAIC in the conception of literacy and the repercussions in teaching practice, indicating the challenges and advances observed and the perceptions of the participating teachers on literacy practice. The results showed that the perceptions of the literacy process and the teaching performance favored a reflection based on the continuing education of literacy teachers and the quality and continuous improvement of teaching and learning of students in the literacy phase. As a product of the Professional Master’s degree in Education, the participation in the organization of the extension course “Literacy and Literacy Practices” offered to literacy teachers during 2019 was prominent.